Predicting postoperative pain with neutrophil/ lymphocyte ratio after arthroscopic rotator cuff repair - Kerim Öner; Ahmet Emin Okutan; Muhammet Salih Ayas; Ahmet Emre Paksoy; Ferdi Polat (Elsevier, 2020)
Background: Postoperative pain is well known and usually disturbing complication of arthroscopic shoulder surgery. Inflammation plays an important role in the development and progression of postoperative pain. The aim of this study was to evaluate the predictability of postoperative pain through the correlation of neutrophil/lymphocyte ratio (NLR) with inflammation. In addition, the correlation of parameters such as operative time, tear size, age and gender with postoperative pain was evaluated. Methods: Sixty three patients, who underwent arthroscopic rotator cuff repair, were evaluated in this single-center-based retrospective study. The American Society of Anaesthesiologists I and II risk groups were determined as the inclusion criteria. NLR was calculated using preoperative one day hemogram values in all patients. The amounts of analgesic use and Numerical Rating Scale (NRS) scores at the 12th, 24th and 48th hours and on the 3rd and 7th days were recorded. Multivariate linear regression analysis was used to correlate postoperative NRS scores with multiple independent factors, including preoperative NLR, sex, age, tear size, repair type, operative time, block time, postoperative analgesic intake and length of hospital stay. Results: Sixty three patients with a mean age of 59.4 years (range, 40-72 years) were evaluated. The mean tear size was 2.8 cm (range, 1-5 cm), the mean operative time was 84.1 min (range, 35-135 min), the mean duration of block was 7.6 hours (range, 4-12 hours) and the mean length of hospital stay was 1.7 days (range, 1-3 days). There was no significant correlation between age, sex, tear size, repair type, operative time and postoperative NRS (p > 0.2). The preoperative NLR was found to be a strong predictor of postoperative NRS (p < 0.001, rho = 0,864). There was a correlation between the NLR and mean analgesic intake (p = 0,03). The duration of block was decreased in patients with a NLR above 2, while it was prolonged in patients with a NLR below 2 (p = 0.04, rho = −0,725). Conclusion: The preoperative NLR was found to be a strongest factor predicting high acute pain levels after arthroscopic rotator cuff surgery. Likewise, NLR was also predictive of postoperative block time and analgesic consumption. Keywords: Arthroscopic, Pain, Rotator cuff tear, Screening, Inflammation